Specific Open-Ended Assessment: Assessing Students' Critical Thinking Skill on Kinetic Theory of Gases - Perdana, Riki; Riwayani, Riwayani; Jumadi, Jumadi; Rosana, Dadan; Soeharto, Soeharto (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
The test of critical thinking skills in specific topics in physics is still rarely. This study aimed to develop a specific test in critical thinking skills in the kinetic theory of gases (CTKTG) and also to assess the students' critical thinking skills. This study used the 4D method (Define, Design, Develop, and Disseminate). The CTKTG test was initially tested in four sample groups: interviews with an expert review (N = 3), professional physics teachers (N = 2), and graduate school students (N = 2), students from secondary schools (N = 29). The test was modified based on the revised results in the initial test. After that, the test was given to a group of students in class XI, who were science students (N = 55). The results showed that internal consistency from the CTKTG test was α = .89 (good). The implementation strategies and tactics are the most difficult aspect of critical thinking skill with a mean of 1.37 (very low) and basic classification is easiest with a mean of 2.84 (average). So, the findings showed that the CTKTG test can be used to measure students' critical thinking skills on the topic of the kinetic theory of gases.